The Role of Environmental-Friendly Factors and Islamic Religiosity in Achieving Sustainable Consumption - Febrina Mahliza; Prita Prasetya; Riska Rosdiana; Putri Dwi Wahyuni (Journal of Consumer Sciences, 2025)
Background: The circular economy aims to establish a sustainable system by maximizing and optimizing resources and capabilities, enabling businesses to provide greater value to consumers. Consumers’ perceptions of environmental values, along with their environmental concerns and knowledge, play a crucial role in encouraging efficient and sustainable consumption. Additionally, individuals with strong religious beliefs often exhibit pro-environmental attitudes, which may influence their intentions and behaviors in purchasing environmentally friendly products.